2012
DOI: 10.1186/1471-244x-12-140
|View full text |Cite
|
Sign up to set email alerts
|

The association between expressed emotion, illness severity and subjective burden of care in relatives of patients with schizophrenia. Findings from an Italian population

Abstract: BackgroundAn appropriate understanding of the association between high-Expressed Emotion (EE) in family members of people with schizophrenia, patients’ and relatives’ correlates is needed to improve adaptation of psychoeducational interventions in diverse cultures. The aim of this study was to test the hypothesis that relatives designated as high EE would report higher subjective burden of care, and would be associated with objective variables that indicate greater illness severity i.e. number of previous hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
35
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 66 publications
7
35
1
3
Order By: Relevance
“…It was found that perceived social support and getting professional support were important determinants of burnout in previous studies (32,33). Perceived social support was associated with all burnout dimensions in our study.…”
Section: Discussionmentioning
confidence: 78%
“…It was found that perceived social support and getting professional support were important determinants of burnout in previous studies (32,33). Perceived social support was associated with all burnout dimensions in our study.…”
Section: Discussionmentioning
confidence: 78%
“…In fact, the family may play a significant role in bipolar disorder, similar to schizophrenia (Magliano et al, 2006a(Magliano et al, , 2006b) and major depression (Luciano et al, 2012a), in which living in a dysfunctional family is associated with more frequent relapses and hospitalizations, lack of compliance, and a worse social functioning (Carrà et al, 2012;Fiorillo et al, 2013a;Viana et al, 2013). Moreover, in bipolar disorders, high levels of family burden can have a detrimental effect not only on patients' long-term outcome, but also on caregivers' quality of life and well-being (Ogilvie et al, 2005;Steele et al, 2010;Pompili et al, 2014).…”
mentioning
confidence: 97%
“…18,19 Relapse rates 20 and duration of untreated first-episode psychosis are associated with family conditions like perceived criticism 21 and emotional over-involvement, both aspects of the high EE concept. 25,26 Nevertheless, general literature on family atmosphere 22,23 suggests that EE is often 24 but not always 25 related to higher relapse rates and criticism is a better predictor than the EE composite score in the long run.…”
Section: Introductionmentioning
confidence: 99%